Impact of low‐dose quetiapine‐use on glycosylated hemoglobin, triglyceride and cholesterol levels. (4th November 2022) - Højlund, Mikkel; Støvring, Henrik; Andersen, Kjeld; Correll, Christoph U.; Hallas, Jesper
Abstract: Objective: Quetiapine use at standard doses has been associated with hyperglycemia and dyslipidemia. However, whether even frequently prescribed low‐dose quetiapine results in significant metabolic disturbances remains unclear. Thus, this study aimed to investigate the association between off‐label, low‐dose quetiapine and changes in glycosylated hemoglobin (HbA1c) levels/lipid parameters. Methods: We identified new users of low‐dose quetiapine (≤50 mg tablets) in Denmark 2008–2018 with measurements of HbA1c, total cholesterol (TC), low‐density lipoprotein cholesterol (LDL‐C), high‐density lipoprotein cholesterol (HDL‐C), or fasting triglycerides (fTG) within 365 days before and after quetiapine initiation. Mixed‐effects linear regression models were used to estimate coefficients (β) with 95% confidence intervals (95%CIs) for change in cardiometabolic parameters after quetiapine initiation. Inverse probability weighting was used to mitigate selection bias. Higher doses of quetiapine (>50 mg) were included in sensitivity analyses. Results: Among 106, 711 eligible new low‐dose quetiapine users (median age = 45 years, females = 55%), low‐dose quetiapine initiation was associated with increased fTG ( β = 1.049[95%CI:1.027–1.072]) and decreased HDL‐C ( β = 0.982[0.978–0.986]). Although HbA1c did not change significantly and TC and LDL‐C even decreased considering all subjects, all three metabolic parameters increased significantly among individuals with normal pre‐quetiapine initiation levels. The adverse metabolic effect of quetiapine on HbA1c, TC, LDL‐C, and HDL‐C was dose‐dependent, which was not the case for fTG. Conclusions: Low‐dose quetiapine was associated with a significant increase in fTG and decreases in HDL‐C in all subjects, as well as with significant increases in HbA1c, TC, and LDL‐C among those with normal baseline values. The risk of metabolic worsening with quetiapine was dose‐dependent, except for fTG.